Association of Malnutrition, Left Ventricular Ejection Fraction Category, and Mortality in Patients Undergoing Coronary Angiography: A Cohort With 45,826 Patients - Mai, Ziling; Huang, Zhidong; Lai, Wenguang; Li, Huanqiang; Wang, Bo; Huang, Sumei; Shi, Yingming; Yu, Sijia; Hu, Qizheng; Liu, Jin; Zhang, Lingyu; Liu, Yong; et al. (Frontiers in Nutrition, 2021)
Background: The regulatory effect of the left ventricular ejection fraction (LVEF) categories on the association of malnutrition and all-cause mortality in patients undergoing coronary angiography (CAG) have not been adequately addressed. Methods: Forty-five thousand eight hundred and twenty-six patients consecutively enrolled in the Cardiorenal ImprovemeNt (CIN) study (ClinicalTrials.gov NCT04407936) from January 2008 to July 2018 who underwent coronary angiography (CAG). The Controlling Nutritional Status (CONUT) score was applied to 45,826 CAG patients. The hazard ratios of mortality across combined LVEF and/or malnutrition categories were estimated by Cox regression models. Variables adjusted for in the Cox regression models included: age, gender, hypertension (HT), DM, PCI, coronary artery disease (CAD), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TRIG), chronic kidney disease (CKD), statins, atrial fibrillation (AF), anemia, and stroke. Population attributable risk (PAR) was estimated for eight groups stratified by nutritional status and LVEF categories. Results: In our study, 42,181(92%) of patients were LVEF ≥ 40%, of whom, 41.55 and 9.34% were in mild and moderate or severe malnutrition status, respectively, while 46.53 and 22.28% in mild and moderate or severe malnutritional status among patients with LVEF < 40%. During a median follow-up time of 4.5 years (percentile 2.8–7.1), 5,350 (11.7%) patients died. After fully adjustment, there is no difference of mortality on malnutrition in LVEF < 40% group (mild, moderate and severe vs. normal, HR (95%CI): [1.00 (0.83–0.98)], [1.20 (0.95–1.51)], [1.41 (0.87–2.29)], respectively, p for trend =0.068), but malnutrition was related to markedly increased risk of mortality in LVEF ≥ 40% group (mild, moderate, and severe vs. normal, HR (95%CI): [1.21 (1.12–1.31)], [1.56 (1.40–1.74)], and [2.20(1.67–2.90)], respectively, p for trend < 0.001, and p for interaction < 0.001). Patients with LVEF ≥ 40% had a higher malnutrition-associated risk of mortality and a higher PAR than those with LVEF < 40%. Conclusions: Malnutrition is common in CAG patients and it has a greater effect on all-cause mortality and a higher PAR in patients with LVEF ≥ 40% than LVEF < 40%.